Cyclic Guanosine Monophosphate–Adenosine Monophosphate Synthase (cGAS), a Multifaceted Platform of Intracellular DNA Sensing - Verrier, Eloi R.; Langevin, Christelle (Frontiers in Immunology, 2021)
Innate immune pathways are the first line of cellular defense against pathogen infections ranging from bacteria to metazoa. These pathways are activated following the recognition of Pathogen Associated Molecular Patterns by membrane and cytosolic Pattern Recognition Receptors. In addition, some of these cellular sensors can also recognize endogenous Danger Associated Molecular Pattern arising from damaged or dying cells and triggering innate immune responses. Among the cytosolic nucleic acid sensors, the cyclic guanosine monophosphate-adenosine monophosphate (cGAMP) synthase (cGAS) plays an essential role in the activation of the type I interferon response and the production of pro-inflammatory cytokines. Indeed, upon nucleic acid binding cGAS synthesizes cGAMP, a second messenger mediating the activation of the STING signaling pathway. The functional conservation of the cGAS-STING pathway during evolution highlights its importance in host cellular surveillance against pathogen infections. Apart from their functions in immunity, cGAS and STING also play major roles in nuclear functions and tumor development. Therefore, cGAS-STING is now considered as an attractive target to identify novel biomarkers and design therapeutics for auto-inflammatory and autoimmune disorders as well as infectious diseases and cancer. Here, we review the current knowledge about cGAS structure and evolution from bacteria to metazoa and present its main functions in defense against pathogens and cancer, in connection with STING. The advantages and limitations of in vivo models relevant for studying the cGAS-STING pathway will be discussed for the notion of species specificity and in the context of their integration into therapeutic screening assays targeting cGAG and/or STING.